Interaksi Hadis dan Budaya Lokal: Living Hadis dalam Tradisi Mattampung Masyarakat Bugis - Aripai, Andi Fatihul Faiz; Amin, Mukhlisah (Journal of Hadith Studies, 2024)
This study examines Mattampung, a traditional death ritual of the Bugis community in Watu Village, Barebbo District, Bone Regency, South Sulawesi. The ritual involves restoring or replacing graves with headstones and is carried out to pray for the deceased. The research is based on the argument that the Mattampung tradition reflects the reception of hadith, particularly those related to the virtues of reciting the Qur’an and offering prayers for the dead, thus shaping the community’s religious practices. This field research adopts a qualitative descriptive approach and was conducted over six months. Primary data were obtained through direct observation, interviews with ten informants, and written and personal documentation. The analysis draws upon the theory of living hadith and Alfred Schutz’s phenomenological framework, which explores human actions through "because of" and "in order to" motives. Findings reveal that Mattampung serves as a form of living hadith, wherein the community internalizes and practices prophetic teachings in a localized religious context. The tradition embodies a dynamic interaction between textual transmission and lived religious experience. From a phenomenological perspective, community motives include preserving cultural heritage, comforting bereaved families, giving charity, and honoring parents. The goals of the ritual are to pray for the deceased, repair graves, educate descendants, deepen religious knowledge, and foster mutual support. Overall, Mattampung illustrates how local Islamic traditions can serve as meaningful expressions of hadith reception and contribute to the preservation of both religious values and cultural identity within the Bugis community.